Clinical usefulness of glycated albumin and glycated albumin-to-glycated hemoglobin ratio of gestational diabetes mellitus in late pregnancy for predicting infant complications - Daisuke Sugawara; Hiroaki Sato; Eishi Makita; Tomoyuki Kuwata; Kenjiro Takagi; Ko Ichihashi (Elsevier, 2022)
Background: Gestational diabetes mellitus (GDM) with poorly controlled glycemia is associated with poor pregnancy outcomes. However, adequate markers for glycemic control in GDM have not been fully evaluated. Methods: We retrospectively studied 77 patients with GDM and their infants. Mean glycated albumin (GA), glycated hemoglobin (HbA1c), and GA/HbA1c in GDM were compared between two groups stratified by the presence or absence of infant complications (complications or non-complications). We assessed the predictability of infant complications in GA, HbA1c, and GA/HbA1c of women with GDM by receiver operating characteristic analysis (ROC). Results: In complications and non-complications, GA and GA/HbA1c were significantly associated with neonatal hypoglycemia (13.9% vs. 13.0%, p < 0.001 and 2.49 vs. 2.33, p < 0.001, respectively), respiratory disorders (13.7% vs. 13.2%, p = 0.013 and 2.48 vs. 2.34, p < 0.001, respectively), myocardial hypertrophy (14.5% vs. 13.0%, p < 0.001 and 2.59 vs. 2.33, p < 0.001, respectively), and large for gestational age (14.5% vs. 13.1%, p < 0.001 and 2.58 vs. 2.34, p < 0.001, respectively). Compared with each infant complication in ROC, GA and GA/HbA1c had higher area under the curve than HbA1c. Especially, GA and GA/HbA1c had highest AUC in predicting myocardial hypertrophy and large for gestational age (GA; 0.92 and 0.92, GA/HbA1c; 0.91 and 0.86, respectively). Although statistically significant positive correlations were found between GA and GA/HbA1c and the number of infant complications (GA: r = 0.417, p < 0.001; GA/HbA1c: r = 0.408, p < 0.001), their correlations were weak. Conclusion: Compared with HbA1c, GA and GA/HbA1c of GDM in late pregnancy might be useful for predicting infant complications arising from GDM.